(3TQM cJGH GdSHYjf GdehGRjfjI aj JQGcjH GdCLSGO hGdEcSjQs - (3LGHQ Hf MjGf Hf YHO Gddg Gdchaj, CHh ehSi, J (B200 (3g` s
(3ChdgG (B:s
(3hHYO , hEf eKGd GdEcSjQ eGFI ef GdYOO heKGd GdPgH YTQhf ef GdYOO heKGd GdaVi YTQI ef GdYOO s
(3Vef eLehY , JQJjHgG (B: (3ef U (B120 - (3U(B130s
(3GdfSNI HgG MhGTs
(3jdjg ebJWaGJ ef HYV cJH LGHQ Hf MjGf hgj (B: (3cJGH GdQMeI cJGH GdKdGKjf cdeIs
(3cJGH Gdefis
(3cJGH GdgOi hgj ef cJGH GdSHYhf s
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
Keywords: (3GdcjejGA h GdWHjYjGJs